Is Interpersonal Psychotherapy Infinitely Adaptable? A Compendium of the Multiple Modifications of IPT - FRANK, ELLEN (Am J Psychother, 2014)
We employed standard literature search techniques and surveyed participants on the International Society for Interpersonal Psychotherapy listserve (isipt-list@googlegroups.com) to catalogue the multiple and highly creative ways in which Klerman’s and Weissman’s original concept of interpersonal psychotherapy (IPT) has been modified to meet the needs of a vast range of patient populations. Focusing first on adaptations of the individual treatment model for subgroups of adult patients, we next describe further adaptations of four major off-shoots of IPT: interpersonal counseling (IPC), IPT for adolescents (IPT-A), group IPT (IPT-G) and most recently, brief IPT (IPT-B). We then discuss IPT “in-laws,” those treatments that have married IPT with of other forms of psychotherapy for patients with bipolar disorder, panic symptomatology, and substance abuse. We conclude with that although there have been myriad successful adaptations of IPT, there remain some conditions for which IPT adaptations have not been found to be efficacious.